Hydatid Cyst Treatment and Management in Retroperitoneal Organs; Is Percutaneous Drainage an Option? Minimally invasive treatment of cyst hydatid - Göger, Yunus Emre; Ozkent, Mehmet Serkan; Yıldırım, Mehmet Aykut; Bakdık, Suleyman; Sönmez, Mehmet Giray; Kadiyoran, Cengiz; Balasar, Mehmet; Cakir, Murat (Urology Journal, 2020)
Purpose: To evaluate patients who cyst hydatid (CH) in their retroperitoneal space and organs in order to determine a standard treatment option for CH. Materials and Methods: The files of 56 patients who were treated for CH in our clinic were evaluated retrospectively. All patients underwent either percutaneous drainage (PD) or surgery. Patients were divided into two groups as PD (Group one) and surgery groups (Group two). Preoperative and postoperative results were compared statistically. Results: 31 of 56 patients were male. Mean age of the patient was 39.7 (10–85). 16 patients had been treated with PD and 40 with different surgical interventions such as total cystectomy, partial cystectomy, partial nephrectomy, total nephrectomy, surrenalectomy, and laparoscopic partial surrenalectomy. Patients’ followed up was 18 months (6-38m). Relapse was seen in 1 patient who underwent PD. On comparing the results, hospitalization period was prolonged in the surgical group with enlarged cyst presence. Conclusion: CH presence in the retroperitoneal area is rare. PD, a minimally invasive method, has the potential to be the standard treatment option as it can be performed safely in selected patients. However, currently surgical treatment is considered as the first treatment option after CH diagnosis.